2009
DOI: 10.1016/j.plaphy.2009.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of SERK, LEC1-Like and Pathogenesis-Related genes during indirect secondary somatic embryogenesis in grapevine

Abstract: A culture model was developed in Vitis vinifera L., cultivar 'Chardonnay' for studying SE (Somatic Embryogenesis). The auxin 2,4-D (2,4-Dichlorophenoxyacetic acid) was used to induce indirect secondary embryogenesis at a high rate, starting from embryos derived from embryogenic cultures previously obtained. Cotyledonary embryos were shown to be more responsive to SE induction than embryos at the torpedo-stage and were used for molecular analyses. The expression of SERK (Somatic Embryogenesis Receptor Kinase), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 65 publications
4
38
0
2
Order By: Relevance
“…The L1L is crucial for proper embryogenesis performance. Its expression was analyzed during SE induction from singlenode Helianthus annuus (Fambrini et al 2006), Theobroma cacao staminodes (Alemanno et al 2008) as well as the stamen and nodal Vitis vinifera (Schellenbaum et al 2008;Maillot at al. 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The L1L is crucial for proper embryogenesis performance. Its expression was analyzed during SE induction from singlenode Helianthus annuus (Fambrini et al 2006), Theobroma cacao staminodes (Alemanno et al 2008) as well as the stamen and nodal Vitis vinifera (Schellenbaum et al 2008;Maillot at al. 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of SERK proteins in regulating somatic embryogenesis was first described for DcSERK in embryogenic cell suspension cultures of carrot more than 15 years ago (Schmidt et al, 1997). Since then SERK gene homologs have been identified and their role in mediating somatic embryogenesis demonstrated in several monocot and dicot species such as Arabidopsis thaliana , Medicago truncatula (Nolan et al, 2003), Triticum aestivum (Singla et al, 2008), Vitis vinifera (Maillot et al, 2009), Cocos nucifera (Pérez-Núñez et al, 2009), Ananas comosus (Ma et al, 2012) and Cyrtochilum loxense (Cueva et al, 2012). Moreover, a gymnosperm SERK homolog has recently been discovered and its association with somatic embryogenesis was shown (Steiner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…32 In Vitis vinifera differential expression of SERK genes was observed concomitantly to some PR proteins upregulated by 2,4-D, a known somatic embryogenesis inducer. 14 On the other hand, it was demonstrated that the auxin naphthalene acetic acid (NAA) was able to upregulate SERK gene in Medicago trucatula. 4 In rice some defense signaling molecules, such as SA and JA, induced SERK upregulation and a slight induction by ABA.…”
Section: Serk As a Broader Signal In Response To Biotic And Abiotic Smentioning
confidence: 99%
“…5 In spite of its role in plant development, different genes from the family showed a different expression pattern during somatic or zygotic embryogenesis 12 and the expression of these genes was differentially detected in different tissues in several plant species, such as in the apical meristem, root and leaves, 5,8,11,13,14 suggesting additional roles for this gene. T-DNA mutational insertions showed the redundancy of two SERK homologs and its role in male sporogenesis in Arabidopsis.…”
mentioning
confidence: 99%